2002
DOI: 10.1161/01.res.0000019242.51541.99
|View full text |Cite
|
Sign up to set email alerts
|

Functional Significance of Prorenin Internalization in the Rat Heart

Abstract: Abstract-Intracardiac renin is considered to be involved in the pathogenesis of cardiac hypertrophy, fibrosis, and myocardial infarction. Cardiac renin is predominantly derived from the circulation, because preprorenin is not expressed locally and uptake of renin has been demonstrated. One mechanism of internalization recently described involves the mannose-6-phosphate receptor and requires glycosylation of renin. Based on previous observations, we considered the existence of another pathway of uptake, not req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
88
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 48 publications
0
88
2
Order By: Relevance
“…2 Important among these new observations are studies demonstrating that (1) prorenin and renin can bind to specific cellular receptors with the generation of physiological effects, (2) prorenin, and to a lesser extent, renin, can be internalized by cells whereupon angiotensin II is produced, and (3) there exists a renin transcript in some cells that encodes a renin that is expected to be synthesized as an active, as opposed to a prorenin, and that is expected to remain in the cell because it lacks the sequence encoding the secretory signal piece (renin exon 1A). [2][3][4][5][6][7][8][9][10][11][12][13] These observations not only reveal prorenin and renin to be hormones in their own right, they suggest that prorenin and renin are intracrines.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…2 Important among these new observations are studies demonstrating that (1) prorenin and renin can bind to specific cellular receptors with the generation of physiological effects, (2) prorenin, and to a lesser extent, renin, can be internalized by cells whereupon angiotensin II is produced, and (3) there exists a renin transcript in some cells that encodes a renin that is expected to be synthesized as an active, as opposed to a prorenin, and that is expected to remain in the cell because it lacks the sequence encoding the secretory signal piece (renin exon 1A). [2][3][4][5][6][7][8][9][10][11][12][13] These observations not only reveal prorenin and renin to be hormones in their own right, they suggest that prorenin and renin are intracrines.…”
mentioning
confidence: 78%
“…1,2,7-19,23-26,32-36 Moreover, a recent study that used transgenic animals expressing nonglycosylated prorenin in the liver demonstrated the uptake and activation of this renin in cardiac myocytes, resulting in enhanced production of angiotensin and the development of cardiac pathology. 7 These observations again raise the possibility that complete intracellular renin-angiotensin systems exist in some cells. [13][14][15][32][33][34][35][36] These intracrine renin-angiotensin systems (iRAS) could offer a new therapeutic target, given the differential ability of various inhibitors to act at intracellular sites.…”
Section: Intracrine Prorenin/reninmentioning
confidence: 97%
“…Inasmuch as HMC-1 are a model of native mast cells, our data suggest that mast cells are capable of renin synthesis in situ and do not acquire renin by internalization of circulating renin. Mast cells are not known to express either the mannose-6-phosphate receptor (33) or renin receptor (34), two possible means by which renin has been postulated to bind to the surface of cells, which could lead to its internalization. Our studies in the HMC-1 cells also rule out this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19] The potential role of intracellular Ang II could be traced back to an early study in which radiolabelled Ang II was found in the nuclei of vascular smooth muscle and cardiac cells following systemic administration. 20 However, Re [25][26][27] Haller et al showed that microinjection of Ang II directly into rat vascular smooth muscle cells increased intracellular calcium, which could be blocked by intracellular AT 1 -receptor blockers.…”
Section: Introductionmentioning
confidence: 99%